PROTEÇÃO SOCIAL ÀS CRIANÇAS INDÍGENAS NO MUNICÍPIO DE PONTA GROSSA – PARANÁ: POSSIBILIDADES E LIMITES NO CAMPO DA REPRESENTAÇÃO - Buzato, Luiz Fernando Taques Fonseca (2013)
For the Brazilian society in general indigenous issues is seen as complex as it seeks to integrate the various indigenous ethnic groups with non-Indian, a nationalist ideological discourse, while preserving their culture starting with abstract conceptions and general on the subject. Symptomatic of this are the various ways of referring to indigenous peoples throughout history, observed both in literature and in the formulation and enforcement of rights. Given this reality, this research aims to study social protection aimed at indigenous children who usually stay overnight in the city of Ponta Grossa in the company of their families in the sale of handicrafts, in order to understand, through the different speeches of representatives of agents government, how they interpret and apply the rights and guarantees to indigenous children. Looking up through these speeches, which grasp concepts and representations that these agents have on indigenous children in the city and how this impacts on social protection, through their practices. To this end, the research uses the literature review as its theoretical support, both to introduce the reader to the field of representation, and to present the image of the Indian construction and their children in Brazil, and to briefly discuss the main conflicts and tensions between Indians and non-Indians in the country's history, the collection of data from the Home Support Indian to know the profile of indigenous families and children who remain there, and field research through informal conversations held with public officials responsible for indigenous issues in the county and collection of their personal testimony through semi-structured questionnaire. Thus, the research will consist of three chapters, in order not only to situate the reader briefly about indigenous issues in Ponta Grossa, but to allow reflection on the possibilities and limits of social protection of indigenous children in the county, through field representations.